Penerapan Metode Indirect Approach Terhadap Software Monitoring Stunting Untuk Menghitung Cost Estimation - Septiana, Fahmi Fadillah; Fikrillah, Hamzah Nurrifqi Fakhri (Jurnal Algoritma, 2025)
The success factor of a software development project is the accuracy of estimating and planning the activities to be carried out, estimating time, cost and quality. Project estimation and planning is required for software to monitor stunting. It is hoped that there is a concept that can calculate the estimated cost of this stunting monitoring software. Therefore, it is necessary to create a method that is able to find out these estimates. Then the function point analysis and use case point methods were chosen to measure and calculate the cost-estimation used as reference parameters at the stunting monitoring software development stage. As a result, an accurate estimate was obtained with the use case point method with the estimated results of 10 people designing and creating stunting monitoring software, then 500 man-hours which means 21 working days with a total cost of $20,000 or around Rp. 311,898,000, -. While the Function Point method obtained an FP value of 413.64, an effort value of 4,558,872 people/hour, and also an LOC of 21,923.